"Organizations’ choices when implementing an Early Intensive Behavioral Intervention program (EIBI)" - Dionne, Carmen; Joly, Jacques; Paquet, Annie; Rousseau, Myriam; Rivard, Mélina (Education Sciences & Society - Open Access, 2017)
"The organizations’ characteristics and choices are essential components of an action plan that favors quality program implementation, a prelude to effectiveness, especially in natural environment. The objectives of this study are to describe the choices made by rehabilitation centers (CRDITED) in the context of a universal community based on Early Intensive Behavioral Intervention program (EIBI) for 2 to 5 year-old children with autism spectrum disorder (ASD) in Québec (Canada). Based on a theoretical evaluation model, a questionnaire was filled out by 15 CRDITEDs, covering the large majority of the Quebec territory but also the Quebec population. Results show a great diversity between the different CRDITEDs. Factors that impact implementation quality are identified. Absence of evidence-based implementation practices and the diversity of the approaches to EIBI are discussed."